SALAFISME DI INDONESIA - Ananda, Rifki Abror; Khamdan, Muh.; Ahmad Khoirul Fata (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2024)
This research examines the dynamics of the Salafism movement in Indonesia. Built on the doctrine of Islamic purification, Salafism has evolved into political and social movements with various forms, such as puritan Salafi, haraki, and jihadi. The study highlights the development of the Salafi movement in Indonesia and its contestation with mainstream Islamic groups such as NU and Muhammadiyah. Using critical discourse analysis, the study explores how the identity and religiosity of the Salafi movement are constructed. It reveals the strategic use of social media by Salafi groups to disseminate their teachings. Social media has become an effective tool for attracting followers, particularly among youth and celebrities involved in the hijrah movement. Despite criticism for being overly textualist and conservative, the Salafi’s religious identity is strongly established through distinct symbols of clothing and rituals. This has led to ideological contestation with mainstream Islamic movements that predate their existence in Indonesia.